International Symposium on Social Sciences, Business, Education and Technology 2025 - Faizan Iza, Zainuddin (International Symposium on Social Sciences, Business, Education and Technology 2025 (ISBET2025), 2025)
It is my great pleasure to welcome all participants to the International Symposium on Social Sciences, Business, Education and Technology 2025 (ISBET 2025) and the International Research Conference on Ecotourism and Agriculture 2025 (IRCETA 2025), proudly organized by Global Academic Excellence (GAE). These conferences serve as dynamic platforms for researchers, academicians, industry experts, practitioners, and students from across the globe to come together, exchange ideas, and present their latest research findings. At GAE, we believe in fostering an inclusive academic environment where innovation and collaboration transcend borders, disciplines, and sectors. ISBET 2025 highlights the integration of knowledge across social sciences, business, education, and technology—four pillars crucial to navigating the challenges of the 21st century. Meanwhile, IRCETA 2025 brings attention to the vital intersection of ecotourism and agriculture, promoting sustainable practices and interdisciplinary research that can support environmental conservation and rural development. We are proud to provide a space that encourages scholarly discourse, networking opportunities, and meaningful collaborations that can contribute to real-world impact. Your participation and insights make these events truly valuable, and we thank you for being part of this academic journey. On behalf of the entire GAE team, I extend my heartfelt appreciation to our keynote speakers, presenters, session chairs, reviewers, and all delegates. May these conferences inspire new perspectives, foster lasting connections, and ignite ideas that will shape a better future.